1996
DOI: 10.1002/eji.1830261217
|View full text |Cite
|
Sign up to set email alerts
|

Polyreactive antigen‐binding B cells in the peripheral circulation are IgD+ and B7

Abstract: Polyreactive antibodies are naturally occurring antibodies, primarily of the IgM isotype, that are capable of reacting with a wide variety of different self and non-self antigens. Previously, we reported that a B cell capable of making polyreactive antibody has Ig receptors on its surface that can bind different antigens. The present investigation was initiated to characterize these polyreactive antigen-binding B cells further. A panel of fluorescein isothiocyanate-labeled antigens (insulin, IgG Fc fragment or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Since PAB cells are present in high number in the peripheral circulation of adults and are the predominant B cell type in cord blood, they are ideally resulted to bind and present endogenous host antigens to T cells. Under some circumstances this might occur without activating the costimulatory molecules B7-1 and B7-2 [14,15,28]. Thus PAB cells may play a role in inducing and/or maintaining immunological tolerance.…”
Section: Discussionmentioning
confidence: 96%
“…Since PAB cells are present in high number in the peripheral circulation of adults and are the predominant B cell type in cord blood, they are ideally resulted to bind and present endogenous host antigens to T cells. Under some circumstances this might occur without activating the costimulatory molecules B7-1 and B7-2 [14,15,28]. Thus PAB cells may play a role in inducing and/or maintaining immunological tolerance.…”
Section: Discussionmentioning
confidence: 96%
“…These natural Abs are involved in the spontaneous recognition of several viruses, such as influenza (2), vesicular stomatitis virus, lymphocytic choriomeningitis virus, and vaccinia virus (28). Natural Abs represent a high percentage of the Ig primary repertoire, being expressed by 10 to 30% of the circulating human B cells (9,10). They are usually polyreactive Ig of the IgM isotype (36) that display a low affinity (18) and react with some self and non-self antigens at different frequencies, depending on the antigen (7,36).…”
Section: Vol 78 2004 Rotavirus Vp6 Reactivity To Naive B Cells In Hmentioning
confidence: 99%
“…Analysis of the B7.1 and B7.2 showed that these molecules were not expressed on B-1 cells from normal mice. Chen et al [23] have revealed that polyreactive B-1 cells expressed high levels of MHC, but little or no B7.1 and B7.2. These findings argue that the lack of costimulatory molecules on B-1 cells is the most likely explanation for their failure to stimulate Ag-specific T cells.…”
Section: Discussionmentioning
confidence: 98%